Does Selective Posterior Tibial Slope Technique in Cruciate-Retaining Total Knee Arthroplasty Result in the Elimination of Posterior Cruciate Ligament Management? - Takashi Nakamura, MD; Ryo Takamatsu, MD; Hideyuki Aoki, MD; Hiroshi Takahashi, MD (Arthroplasty Today, 2024)
In cruciate-retaining total knee arthroplasty (CR-TKA), intraoperative posterior cruciate ligament (PCL) management is necessary because retention of optimum PCL tension with high reproducibility is difficult. If PCL management is not performed appropriately, problems such as postoperative pain, poor range of motion, and a feeling of instability may occur. The posterior tibial slope (PTS) has a major influence on the tension of the PCL in CR-TKA. Changes in femoral posterior condylar offset also influences PCL tension in CR-TKA. We designed a surgical procedure in which the PTS is adjusted in association with the posterior condylar offset during surgery. The postoperative clinical results of the primary total knee arthroplasty 159 knee performed by this procedure were favorable. In addition, none of the knees required management of PCL. In our procedure, PCL management, which is the main problem in CR-TKA, is not necessary, and this may be the main advantage of the new procedure.